Neuro-therapeutic benefits of Centella asiatica on some neurodegenerative diseases: a review - Chiroma, Samaila Musa; Mohd Moklas, Mohamad Aris; Mat Taib, Che Norma; Baharuldin, Mohamad Taufik Hidayat; Jagadeesan, Saravanan; Amom, Zulkhairi; Ibrahim, Bulama (RJPBCS, 2017)
Medicinal herbalism has become popular because of its documented efficacy, synergistic interactions against complex conditions and lesser side effects. CA (CA) is a traditional Ayurveda medicine widely used in India, China, and Malaysia and across countries in south-eastern Asia for treating a range of diseases. The whole plant or its parts (leaf or roots) are used for medicinal purpose and its chemical constituents have been proven scientifically to have neuro-protective, wound healing, anti-inflammatory and antioxidants activities. In this review we have retrieved and evaluated available literatures on neuro-therapeutic properties of CA on neurotoxic and transgenic models of Alzheimer’s diseases (AD), Parkinson’s disease (PD) and Huntington’s disease (HD). The extract was found to have neuroprotective ability through modifying a key signaling pathways and events concerned with neuro-degeneration. Further research is required to discover more bioactive compounds of CA and their exact mode of action.